Insomnia Is Associated With Frequency of Suicidal Ideation Independent of Depression: A Replication and Extension of Findings From the National Health and Nutrition Examination Survey - Simmons, Zach; Erickson, Lance D.; Hedges, Dawson; Kay, Daniel B. (Frontiers in Psychiatry, 2020)
Objective Insomnia is associated with suicidality, although the mechanisms of this association are unclear. This study sought to replicate previous findings showing that insomnia symptoms but not sleep duration are associated with frequency of suicidal ideation in adults. We further investigated whether depression or sleep duration moderates the association between insomnia symptoms and frequency of suicidal ideation. Materials and Methods We used the 2005–2006 cycle of the National Health and Nutrition Examination Survey to replicate previously reported findings from the 2007–2008 cycle. We used ordered logistic regression to determine whether insomnia symptoms were associated with frequency of suicidal ideation independently of depression and other potential confounds. To extend these findings, we tested whether depression or sleep duration moderated the association between insomnia symptoms and frequency of suicidal ideation. We further replicated these findings in parallel analyses using the combined data from the 2005–2006 and 2007–2008 cycles. Results This study replicated previous results showing that insomnia symptoms are associated with frequency of suicidal ideation in the NHANES 2005–2006 cycle (OR = 1.09, p < 0.05), even after adjusting for potentially confounding variables, including depression. Neither depression nor sleep duration moderated this association. Difficulty with sleep maintenance insomnia symptoms were most robustly associated with frequency of suicidal ideation (OR ≥ 1.97, p < 0.05). Sleep duration was not robustly associated with suicidal ideation. Conclusions In this study, we found that insomnia symptoms were uniquely associated with frequency of suicidal ideation. This association cannot be explained by the shared association with depression or sleep duration.